The paternity leave in Peru: a working father´s right or son / daughter´s right? - Kriete Urruchi, Karolina Kira (2021)
This article analyzes the antecedents, foundations and explanatory memorandum of Laws 29409 and 30807, Law that granted the right of paternity leave to workers in public and private activity in Peru and its amendment, respectively. The article also delves into the motivations of Peruvian legislators both at the time of legislating for the first time and in the extension of the days of paternity leave; makes an exhaustive analysis of comparative law; points out the errors or mistakes, which in his opinion, remain in the current law; establishes the reasons why paternity leave has not been the expected success and finally addresses the figure of Parental Leave, differentiating it from Paternity Leave.